Elbow Flexion Contractures in Childhood in Obstetric Brachial Plexus Lesions: A Longitudinal Study of 20 Neurosurgically Reconstructed Infants with 8-Year Follow-up - van der Sluijs, Maaike J.; van Ouwerkerk, Willem-Jan R.; van der Sluijs, Johannes A.; van Royen, Barend J. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2015)
Objective Little knowledge exists on the development of elbow flexion contractures in children with obstetrical brachial plexus lesion (OBPL). This study aims to evaluate the prognostic significance of several neuromuscular parameters in infants with OBPL regarding the later development of elbow flexion contractures.Methods Twenty infants with OBPL with insufficient signs of recovery in the first months of life who were neurosurgically reconstructed were included. At a mean age of 4.6 months, the following neuromuscular parameters were assessed: existence of flexion contractures, cross-sectional area (CSA) of upper arm muscles on MRI, Narakas classification, EMG results, and elbow muscle function using the Gilbert score. In childhood at follow-up at mean age of 7.7 years, we measured the amount of flexion contractures and the upper arm peak force (Newton). Statistical analysis is used to assess relations between these parameters.Results Flexion contractures of greater than 10 degrees occurred in 55% of our patient group. The relation between the parameters in infancy and the flexion contractures in childhood is almost nonexistent. Only the Narakas classification was related to the development of flexion contractures in childhood (p = 0.006). Infant muscle CSA is related to childhood peak muscle force.Conclusion The role of infancy upper arm muscle hypotrophy/hypertrophy, reinnervation, and early elbow muscle function in the development of childhood elbow contractures remains unclear. In this cohort prediction of childhood flexion, contractures were not possible using infancy neuromuscular parameters. We suggest that contractures might be an adaptive process to optimize residual muscle function.
Keywords: obstetrical brachial plexus lesions; elbow flexion contractures; muscle hypotrophy; muscle atrophy; MRI; EMG